2004
DOI: 10.1017/s1464793103006341
|View full text |Cite
|
Sign up to set email alerts
|

Flower visitors and pollination in the Oriental (Indomalayan) Region

Abstract: Current knowledge of flower visitors and pollination in the Oriental Region is summarised. Much less is known about pollination than seed dispersal and the coverage of habitats and taxa in the region is very uneven. The available evidence suggests that pollination in lowland forests is dominated by highly social bees (mainly Trigona and Apis species), with beetles probably the next most important group, followed by other bees and flies. In comparison with the better-studied Neotropics, large solitary bees, mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
115
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(122 citation statements)
references
References 222 publications
(364 reference statements)
2
115
0
5
Order By: Relevance
“…It was identified that Nomia sp. pollinated the plant species that were on the forest floor, in the under storey or in forest gaps with relatively long floral tube, and this was exactly like where and what M. malabathricum were found and looks like [11]. Another species from Apidae family that was found on M. malabathricum is Amegilla zonata (L.), also known locally as the Blue-banded bee.…”
Section: Resultsmentioning
confidence: 81%
“…It was identified that Nomia sp. pollinated the plant species that were on the forest floor, in the under storey or in forest gaps with relatively long floral tube, and this was exactly like where and what M. malabathricum were found and looks like [11]. Another species from Apidae family that was found on M. malabathricum is Amegilla zonata (L.), also known locally as the Blue-banded bee.…”
Section: Resultsmentioning
confidence: 81%
“…The bee fauna of the Indomalayan regions is the poorest (89 genera) in the world compared to the other regions, because the higest bee diversity was in arid temperates regions (Corlett, 2004), however bees are recognized as important pollinators for both crops and wild plants worldwide (Klein et al, 2008;Potts et al, 2010). Most bees are solitary but many nest communally and eusocial species with female castes are found in the families Halictidae and Apidae (Corlett, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Most bees are solitary but many nest communally and eusocial species with female castes are found in the families Halictidae and Apidae (Corlett, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Pollination units, such as flower blossoms or inflorescences (sensu Faegri & van der Pijl 1979), are visited by a large variety of floral visitors (Faegri & van der Pijl 1979;Corlett 2004). Importantly, however, flower visitation does not necessarily mean pollination (Waser et al 1996;Waser et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Later, they were pinned or stored in alcohol, morphotyped and sent to specialists for identification. Classification of insect groups followed Corlett (2004). Performance of the floral visitor as a pollinator was determined through observations of intrafloral behavior, analysis of photographic records, floral morphology and/or the size relationship between flower and visitor.…”
mentioning
confidence: 99%